HUBUNGAN ANTARA ACADEMIC SELF EFFICACY TERHADAP PROKRASTINASI AKADEMIK MAHASISWA PERAN GANDA - Adhisti Harjanto Putri; Wahyuni Kristinawati (Journal of Innovation Research and Knowledge, 2025)
This study aims to determine the relationship between academic self-efficacy and academic procrastination among students who have dual roles of working and studying. Using a quantitative approach with a correlational design, this research involved 277 students working part-time (3-5 hours per day) aged 18-25 years. Data collection utilized the Academic Procrastination Scale (APS) to measure academic procrastination and the Academic Self-Efficacy Scale to assess academic self-efficacy. Data analysis using Pearson's product-moment correlation revealed a significant negative relationship between academic self-efficacy and academic procrastination r = -0.021 and significant p<0,01. Categorization results indicated that the majority of participants had low levels of academic self-efficacy (38.3%) and moderate levels of academic procrastination (42.2%). These findings suggest that the lower the academic self-efficacy of dual-role students, the higher their tendency for academic procrastination. This research has important implications for educational institutions to develop programs aimed at enhancing academic self-efficacy to reduce academic procrastination among part-time working students.